Cuff leak test and laryngeal survey for predicting post-extubation stridor - Anit B Patel; Chizobam Ani; Colin Feeney (Indian Journal of Anaesthesia, 2015)
Background and Aims: Evidence for the predictive value of the cuff leak test (CLT) for post-extubation stridor (PES) is conflicting. We evaluated the association and accuracy of CLT alone or combined with other laryngeal parameters with PES. Methods: Fifty-one mechanically ventilated adult patients in a medical-surgical intensive care unit were tested prior to extubation using; CLT, laryngeal ultrasound and indirect laryngoscopy. Biometric, laryngeal and endotracheal tube (ETT) parameters were recorded. Results: PES incidence was 4%. CLT demonstrated ′no leak′ in 20% of patients. Laryngeal oedema was present in 10% of the patients on indirect laryngoscopy, and 71% of the patients had a Grades 1-3 indirect laryngoscopic view. Mean air column width on laryngeal ultrasound was 0.66 ± 0.15 cm (cuff deflated), mean ratio of ETT to laryngeal diameter was 0.48 ± 0.07, and the calculated CLT and laryngeal survey composite was 0.86 ± 1.25 (range 0-5). CLT and the CLT and Laryngeal survey composite measure were not associated with or predict PES. Age, sex, peri-extubation steroid use, intubation duration and body mass index were not associated with PES. Conclusion: Even including ultrasonographic and indirect laryngoscopic examination of the airway, no single aspect of the CLT or combination with laryngeal parameters accurately predicts PES.